Exploring end-user preferences of 3D mobile interactive navigation design - Abubakar, Adamu; Mantoro, Teddy; Ayu, Media Anugerah; Mahmud, Murni (2011)
The main aim of 3D mobile interactive navigation support is to offer end-users easier means of accomplishing basic and complex navigation tasks in a user friendly way. Unfortunately, not until the end-users make use of the end-product or prototype, their needs, preferences, and their true understanding will not be acknowledged. As a result of these considerations, this paper presents a qualitative interview study to explore the end-users preferences for 3D mobile interactive navigation system, so as to determine design preferences of the application. The study uses a prototype of the design and conducted photo-diary method interviews, where the prototype visual representations is presented to the prospective end-user in support of an interview, which makes the interview more concrete. The result of the study provided clues about the features that were not foreseen in the earlier design process, the features that need to be upgrade and the features that end-users value most.